2018
DOI: 10.1063/1.5020192
|View full text |Cite
|
Sign up to set email alerts
|

Field induced decrystallization of silicon: Evidence of a microwave non-thermal effect

Abstract: It is rather strange and not fully understood that some materials decrystallize when exposed to microwave radiation, and it is still debatable if such a transformation is a thermal or non-thermal effect. We hereby report experimental evidences that weight the latter effect. First, a single crystal silicon wafer exposed to microwaves showed strong decrystallization at high temperature. Second, when some areas of the wafer were masked with metal coating, only the exposed areas underwent decrystallization. Transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…In another independent experiment involving MWR heating of a single crystal of silicon, which was partially covered with metallic foils, the authors observed that the exposed part of silicon became amorphous, whereas the covered region remained crystalline. It was suggested that rapid heating under MWR results in random displacement of atoms, thus creating lattice strain . This decrystallization, or the formation of the amorphous phase, can also be thought of as a highly distorted lattice structure due to a high concentration of defects (vacancies and interstitials).…”
Section: Resultsmentioning
confidence: 99%
“…In another independent experiment involving MWR heating of a single crystal of silicon, which was partially covered with metallic foils, the authors observed that the exposed part of silicon became amorphous, whereas the covered region remained crystalline. It was suggested that rapid heating under MWR results in random displacement of atoms, thus creating lattice strain . This decrystallization, or the formation of the amorphous phase, can also be thought of as a highly distorted lattice structure due to a high concentration of defects (vacancies and interstitials).…”
Section: Resultsmentioning
confidence: 99%
“…The PFT of S7 and S8 increased by 13.7% (S9) and 42% (S10) respectively after microwave processing (Figure 5c). The improved thermoelectric PFT of the microwave processed samples in comparison to SPS samples is also due to the non-linear transport of charge carriers between the decrystallized grains with compositional variation and/or disordered-crystalline regions [42,43,44].…”
Section: Resultsmentioning
confidence: 99%
“…An example for the former is field-driven decrystallization of materials. 23,24,55,56 Bottom panel in Figure 3a shows an x-ray diffraction pattern, where the sharp peaks indicate crystalline anatase TiO 2 . 56 When exposed to time-varying microwave radiation at 2.45 GHz, peak intensity decreases drastically, indicating decrystallization.…”
Section: Fundamental Questions-atomistic Structural Changes Under Electric and Electromagnetic Fieldsmentioning
confidence: 99%